Magnetic-pulsed attraction of sheet billets with “direct passage of current” - Batygin, Yuriy; Yeryomina, Olena; Shinderuk, Svitlana; Strelnikova, Viktoria; Chaplygin, Evgeniy (Національний технічний університет "Харківський політехнічний інститут", 2020)
The theoretical substantiation of the efficiency of magnetic-pulse attraction method of sheet metal with “direct current transmission” through the object being processed is presented. The analysis of well-known works in this area is carried out, it is shown that the lack of sufficiently complete theoretical studies does not allow effectively performing a given production operation. By solving the boundary-value electrodynamic problem, analytical expressions are obtained for the phase dependences of currents in the experimental system and the excited forces of attraction of the processed object. It is proved by numerical estimates that the low-frequency mode of the ongoing electromagnetic processes is preferable when the fields penetrate intensively through the condu cting components of the system under study. It was found that the calculated dependence of the developed forces on the discharge voltage of the capacitive storage allows an approximate estimate of the efficiency of attraction when operating in the accepted range of energy capabilities of the power source. It is shown that the degree of inhomogeneity of the transverse distribution of attractive forces in the region under study does not exceed ~ 20%. A working experimental model has been designed and created, consisting of a tool for magnetic-pulse attraction of sheet metal and a power source - an energy unit. Based on the obtained ratios, the characteristics of the pilot plant and the test modes were calculated. A dosed magnetic-impulse force action has been practically implemented, which makes it possible to control the deformation of sheet metal in the processing zone. Experiments have been carried out to remove dents on samples made of various types of steel under conditions close to the corresponding real production operation. The practical possibilities of the means of magnetic-pulse attraction of certain sections of sheet metals with “direct current transmission” through them have been successfully demonstrated. The effectiveness of the method under consideration is proved when using the indicators of the technological operation, calculated based on theoretically obtained dependences.

Представлено теоретичне обґрунтування працездатності методу магнітно-імпульсного притягання листового металу з «прямим пропусканням струму» через оброблюваний об'єкт. Проведено аналіз відомих робіт в цій галузі, показано, що відсутність досить повних теоретичних досліджень не дозволяє ефективно виконувати задану виробничу операцію. Шляхом вирішення крайової електродинамічної задачі отримані аналітичні вирази для фазових залежностей струмів в експериментальній системі і порушених сил притягання оброблюваного об'єкта. Доведено чисельними оцінками, що низькочастотний режим електромагнітних процесів, що протікають, кращий при інтенсивному проникненні полів через провідні компоненти досліджуваної системи. Встановлено, що розрахована залежність сил, що розвиваються, від напруги розряду ємнісного накопичувача дозволяє приблизно оцінити ефективність притягання при роботі в прийнятому діапазоні енергетичних можливостей джерела живлення. Показано, що ступінь неоднорідності поперечного розподілу сил притягання в досліджуваній області не перевищує ~ 20%. Спроектована і створена діюча експериментальна модель, що складається з інструменту магнітно-імпульсного притягання листового металу і джерела живлення - енергетичного блоку. На основі отриманих співвідношень розраховані характеристики дослідної установки та режими проведення випробувань. Практично реалізовано дозований магнітно-імпульсний силовий вплив, що дозволяє контролювати деформацію листового металу в зоні обробки. Були проведені експерименти з усунення вм'ятин на зразках, виготовлених з різних видів стали в умовах, наближених до відповідної реальної виробничої операції. Успішно продемонстровані практичні можливості засобів магнітно-імпульсного притягання певних ділянок листових металів при «прямому пропущенні струму» через них. Доведено ефективність розглянутого методу при використанні показників технологічної операції, розрахованих на підставі теоретично отриманих залежностей.
Магнітно-імпульсне притягання листових заготовок при «прямому пропусканні струму»
Keywords: experimental approbation; flattening automobile bodies; експериментальна апробація; сплющування автомобільних кузовів